The English workhouse - Hitchcock, T; Hitchcock, Timothy (1985)
This thesis charts the course of the eighteenth-century workhouse movement from the foundation of the Bristol Corporation of the Poor in 1696 to mid-century. It is divided roughly in two. Chapters 2 and 3 deal with the attempted national and parliamentary reforms of the 1690s and 1700s and the collateral local moves towards the creation of Corporations of the Poor. Chapter 2 examines the activities of the Board of Trade and various individual parliamentarians, while chapter 3 looks at four examples of Corporations, those at Bristol, Exeter, London and Norwich. The rest of the thesis deals exclusively with the parochial workhouse movement. Chapters 4 and 8 chart the spread of parochial houses from early centres of activity in the East Midlands and Essex. They also describe and assess the roles of the Society for the Promotion of Christian Knowledge and Matthew Marryott in providing services to early workhouses and in encouraging parishes to set up their own institutions. The role of the S.P.C.K. as a publishing house, political influence and advice centre are each discussed and that of Marryott as both expert and workhouse contractor examined. Chapter 4 also describes and analyses the content and importance of the Workhouse Test Act. Chapters 5, 6 and 7 look at the workhouse movement thematically, examining, in turn, the administration of workhouses, the conditions in these institutions, the make-up of workhouse populations and the reaction of the poor to these houses. In dealing with each of these subjects attention has been paid to the discrepancies which existed between the ideal workhouse conditions laid down by parish vestries and workhouse committees in sets of rules and regimen and the realities of workhouse administration and life exemplified by receipts, inventories and workhouse scandals. Two appendixes have also been produced. The first lists all of the workhouses the location and date of foundation of which have been identified, and the second, all of the houses positively associated with Matthew Marryott either in the role of advisor or contractor.